EJACULATE QUALITY AND CONSTRAINTS IN RELATION TO SPERM COMPETITION LEVELS AMONG EUTHERIAN MAMMALS. (22nd May 2013) - Lüpold, Stefan
<x xml:space="preserve">Abstract</x> The outcome of sperm competition is influenced by the relative quantity and quality of sperm among competing ejaculates. Whereas it is well established that individual ejaculate traits evolve rapidly under postcopulatory sexual selection, little is known about other factors that might influence the evolution of ejaculates. For example, the metabolic rate is likely to affect the sperm production rate and the cellular activity or metabolism of sperm, and it has recently been suggested to constrain the evolution of sperm length in large but not small mammals. I thus examined in eutherian mammals how ejaculate quality traits vary with one another and with testis mass, body size, and metabolism. I found all ejaculate traits to covary positively with one another and to increase with relative testis mass. When controlling for testis mass, small‐bodied species showed superior sperm quality (but not sperm number). Furthermore, sperm motility and viability were positively associated with the mass‐corrected metabolic rate, but the percentage of morphologically normal and acrosome‐intact sperm were not. These results indicate that body size and the energy budget may also influence the evolution of ejaculate quality, although these influences appear to vary among traits.